HIGH SCHOOL STUDENTS’ PERSPECTIVES, GAMING HABITS, LEARNING EXPERIENCES, AND ENGLISH ACHIEVEMENT IN USING COMMERCIAL DIGITAL GAMES FOR ENGLISH LANGUAGE LEARNING - Sonia - Wulandayanti; Suciana - Wijirahayu (Universitas Muhammadiyah Metro, 2026)
The increasing use of commercial digital games in students’ daily activities provides opportunities for informal English language exposure in meaningful contexts. This study aims to explore students’ perceptions of the use of commercial digital games in supporting English learning. This study employed a descriptive quantitative design supported by qualitative data involving 283 senior high school students. Data were collected through an online questionnaire consisting of closed-ended and open-ended questions distributed via Google Forms. The data were analyzed using descriptive statistics with the support of qualitative thematic analysis. The findings show that students generally have positive perceptions of digital games, particularly in enhancing motivation, vocabulary development, and confidence in using English. Students also experience contextual language exposure through instructions, dialogues, and interactions during gameplay. However, challenges were identified, including difficulties in understanding unfamiliar vocabulary and game instructions. Overall, commercial digital games can serve as effective informal learning resources that complement formal instruction. The findings imply that integrating students’ digital gaming experiences into classroom learning may support more meaningful language learning.